Diagnostic and phylogenetic utility of the first DNA barcode library for longhorn beetles (Coleoptera: Cerambycidae) from the Russian Far East - Grebennikov, Vasily V.; Jendek, Eduard; Smirnov, Maxim Ed. (Zootaxa, 2017)
One hundred forty two specimens representing 56 species of longhorn beetles (Cerambycidae) from the Russian Far East were sequenced for a 658 bp fragment of the 5' end of the mitochondrial cytochrome oxidase subunit I gene (COI, =DNA barcode). The data are publicly available in an open access online library (dx.doi.org/10.5883/DS-CERRF). All analysed species could be differentiated using the standard online DNA barcode identification tool, except for a group of three sympatric colour-defined Menesia species. Seven Menesia records share the same Barcode Identification Number (=BIN), while the single specimen of M. flavotecta shares the same haplotype as some of M. sulphurata. Excluding the Menesia case, the Barcode Index Numbers (BINs) uniquely correspond to the analysed species, in all but the four specimens of Chlorophorus simillimus where they share two BINs. Although DNA barcoding aims to develop species identification systems, some phylogenetic signal was apparent in the data and in the Maximum Likelihood analysis, all four subfamilies were recovered as monophyletic. Notwithstanding the few detected deviations from the absolute taxonomic/phylogenetic match, DNA barcoding is a powerful identification tool with a capacity to place an undocumented record among its closest relatives.